Abandono familiar y sus consecuencias en el estado emocional de un adulto mayor de 75 años de edad del Centro Gerontológico de Guaranda - Yánez Lara, Angel Israel (2022)
The present case study is focused on exposing the situation that an adult over 75 years of age from the Guaranda gerontological center is going through due to family abandonment and what are the consequences on the emotional state. In which the consequences of family abandonment in an adult over 75 years of age on her emotional state will be investigated. Considering that the elderly are going through a stage of vulnerability in which they degenerate and lose individual autonomy, for which family support becomes a primary factor for the care and conservation of the elderly since it is found in many of the occasions in danger for different reasons and in many of them it is due to the abandonment of their relatives for not knowing how to deal with their older adult. For the investigation and data collection of this case study, a mixed approach method will be used, using techniques such as: clinical interview, clinical observation, application of psychometric tests with the sole purpose of collecting data relevant to the present problem.